Influence of Tool Shape on Lattice Rearrangement under Loading Conditions Reproducing Friction Stir Welding; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Konovalenko I. S. Ivan Sergeevich (2015, 2015)
Title screen